Regulation of epithelial‐to‐mesenchymal transition in hypoxia by the HIF‐1α network - Wang, Hang‐Yu; Zhang, Xiao‐Peng; Wang, Wei (FEBS letters, 2022)
Epithelial‐to‐mesenchymal transition (EMT) plays a significant role in cancer metastasis. A series of models have focused on EMT regulation by TGF‐β network. However, how EMT is regulated under hypoxia is less understood. We developed a model of HIF‐1α network to explore the potential link between EMT and the network topology. Our results revealed that three positive feedback loops, composed of HIF‐1α and its three targets SNAIL, TWIST, and miR‐210, should be sequentially activated to induce EMT under aggravating hypoxia. We suggested that the number of the positive feedback loops is critical for determining the number of stable states in EMT. Our work may advance the understanding of the significance of network topology in the regulation of EMT. This study reveals the mechanism of hypoxia‐induced epithelial‐to‐mesenchymal transition (EMT) by modeling. Under aggravating hypoxia, hypoxia‐inducible factor‐1α (HIF‐1α) induces snail, twist, and miR‐210 so that three positive feedback loops are triggered sequentially to push forward EMT. Our results suggested that the number of positive feedback loops may be associated with the number of stable states in EMT.